The letters - Klein, A. M. (Abraham Moses), 1909-1972 (Klein, A. M. (Abraham Moses), 1909-1972. Works. 1983., 2011)
In the final volume of the Collected Works of A.M. Klein, Elizabeth Popham completes the process of restoring the public voice of one of Canada's most respected authors. A.M. Klein: The Letters is the first compilation of a significant body of Klein's correspondence. Using his communications to construct a compelling narrative, Popham traces Klein's career from his apprenticeship to great critical success and his tragically premature silence.